1998
DOI: 10.1002/j.2050-0416.1998.tb00974.x
|View full text |Cite
|
Sign up to set email alerts
|

DETECTION AND IDENTIFICATION OFLACTOBACILLUS LINDNERIFROM BREWERY ENVIRONMENTS

Abstract: Ten detection media and six cultivation techniques were evaluated for the detection of a harmful brewery contaminant, for which the name Lactobacillus lindneri was recently revived. These bacteria showed slow and weak growth on solid media. However, enrichment of beer with NBB‐C or the use of a mixture of MRS and beer (4:1 v/v) reduced the detection time by 2 days or more, depending on the strain, compared to cultivation on solid brewery media. Eight brewery isolates from different origins, the type strain and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Medium performance for enrichment of beer-spoiling LAB has been reported in several studies 2,12,13,[19][20][21]23 . However, these studies do not include an assessment of individual growth factors.…”
Section: Introductionmentioning
confidence: 82%
“…Medium performance for enrichment of beer-spoiling LAB has been reported in several studies 2,12,13,[19][20][21]23 . However, these studies do not include an assessment of individual growth factors.…”
Section: Introductionmentioning
confidence: 82%
“…lindneri has been reported to be the second most frequent cause of microbiological incidents by beer spoilage LAB (2, 3). So far, nonspoilage strains of L. lindneri have not been found (17,29), leading to the widespread belief that beer spoilage ability is an innate character of L. lindneri. In this study, we attempted to isolate hop-sensitive variants of L. lindneri DSM 20690 T and DSM 20692.…”
Section: Discussionmentioning
confidence: 99%
“…lindneri has been reported to be the second most frequent beer spoilage species of LAB (2,3). So far nonspoilage strains of L. lindneri have not been found (17,29) and some brewing microbiologists argue that, unlike other beer spoilage species of LAB, L. lindneri is an innate beer spoiler. In this study, we isolated a hop-sensitive variant of L. lindneri DSM 20692 and carried out genetic characterization of this strain, leading to new insights into the character of the ORF 1 to 7 region.…”
mentioning
confidence: 99%
“…Although this method and instrument were originally developed to identify the food-borne pathogens, Listeria, Salmonella, and Staphylococcus spp. and E. coli, it has since been used for many applications, including the identification of spoilage bacteria in the brewing industry (3,(5)(6)(7)(8)10 Org., p. 16, 1998). The manufacturer has demonstrated with food-borne pathogens that the method is close to 100% accurate at identifying genus and species and often has the ability to differentiate at the subspecies level.…”
mentioning
confidence: 99%
“…In a study by Motoyama et al (6), ribotyping was shown to be useful in identifying brewery Lactobacillus isolates to the subspecies level. However, Storgards and Suihko (10) showed that a number of Lactobacillus lindneri isolates were ribotyped and shown to have almost no variation in their riboprint patterns. This could mean that the technology is not adequate to subspeciate this particular organism or that the organism shows very little genetic variation.…”
mentioning
confidence: 99%